Bactericidal Activity of Resin-Titanium Dioxide and Ultraviolet in Killing Escherichia Coli Bacteria - Budiprasojo, Azamataufiq; Erawantini, Feby (Universitas Negeri Semarang, 2021)
Escherichia coli (E.Coli) harms the environment in human digestion. E coli causes diarrhoea if one consumes food or drink that is not clean or exposed to bacteria. This research aims to produce a specimen that combines resin coated with TiO2 and partly ultraviolet light to kill Escherichia coli bacteria. The method used in this research is experimental. The activity in this research is mixing TiO2 nanomaterial with resin, then varying the time and exposure to ultraviolet radiation. Furthermore, observations were made by comparing the number of bacteria found in the two specimens with SEM. Specimens were analyzed using digital image processing. The appearance of the white capsule is the bacteria. The grey bottom is the specimen conclusion in this study was that the TiO2 (titanium dioxide) and resin specimens and modified ultraviolet radiation were quite effective in killing E.coli which achieved a 91% reduction in the number of bacteria.